MYTHOS AND ADAPTATION: THE RĀMĀYAṆA'S JOURNEY TO THE RAMAKIEN - Fiza Chandiwala (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2025)
A timeless Indian epic, the Rāmāyaṇa evolved into diverse localised forms throughout Southeast Asia, transcending cultural and geographic boundaries. The Ramakien of Thailand stands out among them as a striking example of the epic's versatility and timeless appeal. The primary focus of this study,